The Influence of the Family Environment On Student Learning Motivation at SDN 1 Pinrang - Nasrul Nasrul; Muhammad Junaidi Mahyudin; Dedi Setiawan (Universitas Muhammadiyah Enrekang, 2024)
This study aims to analyze the influence of family environment on student learning motivation at SDN 1 Pinrang, focusing on parental support, family socioeconomic conditions, and communication patterns within the family. The research method employed was a quantitative approach with correlational design, involving 120 fourth and fifth-grade students as respondents selected through stratified random sampling technique. The research instrument consisted of structured questionnaires to measure family environment variables and student learning motivation that had been validated and tested for reliability. Data analysis techniques used multiple linear regression analysis with SPSS version 26.0 to examine relationships between variables. The results showed a positive and significant influence between family environment and student learning motivation with a coefficient of determination of 0.724, meaning 72.4% of the variation in student learning motivation can be explained by family environment variables. Partially, parental support provided the largest contribution to student learning motivation with a beta value of 0.458, followed by family communication patterns with beta 0.312, and family socioeconomic conditions with beta 0.198. The research conclusion indicates that family environment is a very important determinant factor in shaping elementary school students' learning motivation, thus requiring collaborative efforts between schools and families to optimize student academic achievement.